Designing Procedure for Evaluating the Fulfillment of Airlines Financial Commitments to MRO Companies - Iriansyah, Cesario
Airlines as the main customer of MRO industries have a major influence on the MRO business operation, because MRO companies require a stable revenue to maintain the continuity of their business operations. Therefore, MRO companies need a procedure to determine the level of compliance of airlines' financial commitments which will be used to assess future cooperation contracts with airlines. MRO XYZ does not have yet a procedure to assess the level of compliance of airlines' financial commitments. This research aims to develop a procedure to assess the compliance of airlines' financial commitments based on financial ratios and the ratio of financial liabilities to operating expense. The method of selecting financial ratios as assessment criteria uses analytic hierarchy process. The criteria value of financial ratios in this procedure is based on the achievements of the airline industry. The data used comes from the annual reports of each airline. The validation of the developed procedure uses actual data of MRO XYZ customers in complying their financial commitments. The results of the research show that the financial ratios cannot be used to assess the compliance of airlines' financial commitments. The level of compliance of airlines' financial commitments can be shown more by using the ratio of financial liabilities to operating expense. It is recommended to add qualitative analysis to make the assessment more accurate.